Potential involvement of circulating extracellular vesicles and particles on exercise effects in malignancies - Siqueira, Ionara Rodrigues; Batabyal, Rachael A.; Freishtat, Robert; Cechinel, Laura Reck (Frontiers in Endocrinology, 2023)
Physical activity and exercise have been widely related to prevention, treatment, and control for several non-communicable diseases. In this context, there are innumerous pre-clinical and clinical evidence indicating the potential role of exercise, beyond cancer prevention and survival, improved quality of life, including on psychological components, bone health and cachexia, from cancer survivors is described as well. This mini review raises the potential role of circulating extracellular and particles vesicles (EVPs) cargo, as exerkines, conducting several positive effects on adjacent and/or distant tissues such as tumor, immune, bone and muscle cells. We highlighted new perspectives about microRNAs into EVPs changes induced by exercise and its benefits on malignancies, since microRNAs can be implicated with intricated physiopathological processes. Potential microRNAs into EVPs were pointed out here as players spreading beneficial effects of exercise, such as miR-150-5p, miR-124, miR-486, and miRNA-320a, which have previous findings on involvement with clinical outcomes and as well as tumor microenvironment, regulating intercellular communication and tumor growth. For example, high-intensity interval aerobic exercise program seems to increase miR‐150 contents in circulating EVPs obtained from women with normal weight or overweight. In accordance circulating EVPs miR-150-5p content is correlated with prognosis colorectal cancer, and ectopic expression of miR-150 may reduce cell proliferation, invasion and metastasis. Beyond the involvement of bioactive miRNAs into circulating EVPs and their pathways related to clinical and preclinical findings, this mini review intends to support further studies on EVPs cargo and exercise effects in oncology.